Correlations Frequency of Exercise with Blood Sugar Levels of Members of the Hatha Yoga Club - Adinda Muji Lastari; Widyatuti Widyatuti (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
Type II diabetes mellitus is a disease that has an increasing prevalence rate every year. The community is urged to make prevention and treatment efforts to reduce complication risks. One of them is the Hatha Yoga exercise, which is a type of yoga that focuses the movement on pancreas health. The purpose of this study is to see the correlation between the frequency of exercise and the blood sugar level of Hatha Yoga club members. The study implements descriptive analytics with a cross-sectional approach on 84 Hatha Yoga club members in a yoga institution. Data collection was done using a questionnaire consisting of demographic data as well as blood sugar values before and after exercises and observations during exercise. Data results were analyzed using SPSS statistic 25 of the One Way Anova test shows a value of (p = 0,0001; p <0,05) thus indicating a meaningful relationship between the frequency of exercise and the blood sugar level of Hatha Yoga club members.